The Causal Relationships Between Extrinsic Exposures and Risk of Prostate Cancer: A Phenome-Wide Mendelian Randomization Study - Gu, Dongqing; Tang, Mingshuang; Wang, Yutong; Cui, Huijie; Zhang, Min; Bai, Ye; Zeng, Ziqian; Tan, Yunhua; Wang, Xin; Zhang, Ben (Frontiers in Oncology, 2022)
Background: Prostate cancer is the second most common cancer in males worldwide, and multitudes of factors have been reported to be associated with prostate cancer risk. Objectives: We aim to conduct the phenome-wide exposed-omics analysis of the risk factors for prostate cancer and verify the causal associations between them. Methods: We comprehensively searched published systematic reviews and meta-analyses of cohort studies and conducted another systematic review and meta-analysis of the Mendelian randomization studies investigating the associations between extrinsic exposures and prostate cancer, thus to find all of the potential risk factors for prostate cancer. Then, we launched a phenome-wide two-sample Mendelian randomization analysis to validate the potentially causal relationships using the PRACTICAL consortium and UK Biobank. Results: We found a total of 55 extrinsic exposures for prostate cancer risk. The causal effect of 30 potential extrinsic exposures on prostate cancer were assessed, and the results showed docosahexaenoic acid (DHA) [odds ratio (OR)=0.806, 95% confidence interval (CI): 0.661-0.984, p=0.034], insulin-like growth factor binding protein 3 (IGFBP-3) (OR=1.0002, 95%CI: 1.00004-1.0004, p=0.016), systemic lupus erythematosus (SLE) (OR=0.9993, 95%CI: 0.9986-0.99997, p=0.039), and body mass index (BMI) (OR=0.995, 95%CI: 0.990-0.9999, p=0.046) were associated with prostate cancer risk. However, no association was found between the other 26 factors and prostate cancer risk. Conclusions: Our study discovered the phenome-wide exposed-omics risk factors profile of prostate cancer, and verified that the IGFBP-3, DHA, BMI, and SLE were causally related to prostate cancer risk. The results may provide new insight into the study of the pathogenesis of prostate cancer.